Carotenoids - Sliwka, Hans-Richard (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Carotenoids are a group of natural pigments, consisting of more than 750 compounds. They are mostly yellow, orange, or red in color, due to the system of conjugated double bonds. This structural element is also responsible for the good antioxidant properties of many carotenoids. Carotenoids have shown numerous biological activities (not only as provitamin A), e.g., preventive properties of fruits and vegetables. As lipophilic compounds, their uptake and storage in the body are dependent on various conditions. In vitro and in vivo data showed stimulating and inhibitory effects of matrix compounds on bioaccessibility and bioavailability of carotenoids.